KEBIJAKAN PERLINDUNGAN LAHAN PERTANIAN PANGAN BERKELANJUTAN ALIH FUNGSI LAHAN DI DESA KEMUNING MUDA KECAMATAN BUNGA RAYA KABUPATEN SIAK - Rizka Rahmadiah; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
To set the land conversion in Siak district, then Siak District Government to formulate a policy regarding land conversion contained in the Regional Regulation No. 2 of 2014. In addition, the law No. 12 of 2014 on article 61 has also been poured clearly that each person doing the compulsory land conversion of agricultural land to restore sustainable food land to its original state. However, the reality in the field there are 79 hectares of agricultural land were transformed to enable rice into oil palm plantations carried out by farmers' groups combined. Land conversion is done in stages commencing in 2006 until 2015. Although, the rules have been there, but that happens in the village Kemuning Muda there are still those who undergo rice farming land conversion to oil palm plantations of the year ketahun increased. The purpose of this study was to determine and analyze why the regulations are not able to realize the results of the policy. The place where you are investigating is Desa Kemuning Muda District of Bungaraya Siak. Who became informants in this study are those directly involved in the implementation of policies that Assembly Members Siak, Head of Agricultural Department of Horticulture and Food Crops Siak, Head UPTD Agriculture District of Bunga Raya, Head Bunga Raya, the Village Head Kemuning Muda, Secretary Desa Kemuning Muda Head of Hamlet I Tani Mukti, Head of Hamlet II Tani Jaya, Head of Dusun III Suka Tani and Society. From the research that I did then obtained some conclusion that the implementation of policies to ensure food security and land use to non-agriculture so far is not yet effective this is because it turns farmers feel that the government has failed to convince them because the policy is considered not to touch on the roots problems, because the existing policy was not able to supply those so that people choose to sell their land, in other words the government failed in implementing policies that exist. Pelaksaanan agricultural land use policies beyond agriculture so far have not been optimal because no policy intervention from the government so that policies do not run optimally. Barriers arising in the implementation of land use policies are obstacles still lack the awareness level of government in the implementation of this policy. Besides power socialization is lacking so that its implementation is still very slow. On the other hand coordination among government agencies is still very less intensive government do this is because the government tends to fall asleep with the existing land.Keywords : Policy, Land Conversion